2014
DOI: 10.1134/s1068162014050112
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Staphylococcus aureus toxins using immuno-PCR

Abstract: A highly sensitive test system, based on the method of immuno-PCR, was developed for the detection of two staphylococcal toxins: enterotoxin A (SEA) and toxic shock syndrome toxin (TSST). A key element of the developed systems was obtaining supramolecular complexes of bisbiotinylated oligodeoxynucleotides and streptavidin, which were used as DNA tags. Specificity studies showed no cross-reactivity when determining SEA and TSST. The sensitivity of detection of these toxins in the culture supernatants S. aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…LAMP has become a powerful tool to detect foodborne pathogens since it was developed (Maerle et al, 2014;Wang et al, 2007Wang et al, , 2008. Yang et al (2011) previously reported that the sensitivity of LAMP in detecting S. aureus was 1.25 CFU per reaction tube and 10.3 CFU per reaction in the artificial contamination test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LAMP has become a powerful tool to detect foodborne pathogens since it was developed (Maerle et al, 2014;Wang et al, 2007Wang et al, , 2008. Yang et al (2011) previously reported that the sensitivity of LAMP in detecting S. aureus was 1.25 CFU per reaction tube and 10.3 CFU per reaction in the artificial contamination test.…”
Section: Discussionmentioning
confidence: 99%
“…However, these assays are relatively complicated and time-consuming. Therefore, more rapid and simple methods are warranted, mainly includes immunology and molecular biology (Amani et al, 2015;Chen et al, 2015;Maerle et al, 2014;Nouri et al, 2018;Shao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard for the isolation and identification of foodborne pathogens is the traditional culture method, which is time consuming (5-7 d) and laborious. Additionally, many methods such as real-time PCR (Caliendo, 2011;Chiao et al, 2013;Maerle et al, 2014) and ELISA (Pauly et al, 2009;Jenko et al, 2014;Liang et al, 2015;Guo et al, 2016) have been developed to screen food-borne pathogens. A series of detection techniques, including GC (Amelin et al, 2013), HPLC (Manetta et al, 2005;Muscarella et al, 2007;Shi et al, 2011), liquid chromatography-MS (Tittlemier et al, 2009;Han et al, 2015;Andjelkovic et al, 2016), ELISA (Vdovenko et al, 2014;Chen et al, 2016b;Liang et al, 2016), and electrochemistry (Micheli et al, 2005;Parker et al, 2009;Cheng et al, 2014;Zhou et al, 2014a) have been established for the analysis of chemical contaminants such as mycotoxins and veterinary drugs.…”
Section: Introductionmentioning
confidence: 99%
“…одноцепочечных олигонуклеотидов, биотинилированных с 5′-и 3′-концов, и стрептавидина. Использование подобных надмолекулярных комплексов позволяет усилить специфический сигнал за счет того, что на одну молекулу ДА приходятся десятки, а то и сотни молекул ДНК-метки; кроме этого важно, что такая система универсальна [23,36].…”
unclassified
“…с соавторами были разработаны надмолекулярные комплексы бисбиотинилирован-ных олигодеоксинуклеотидов со стрептовидином, которые были использованы в качестве ДНК-метки в тест-сиcтеме для определения SEA и TSST. Чувствительность при определении токсинов в супернатантах культур S.aureus составила не менее 10 пг/мл, при 100% специфичности [23,26].…”
unclassified